HISTOMORPHOMETRIC EVALUATION OF POLYP AND PAPILLOMA TISSUES IN THE HUMAN URINARY BLADDER - Shodiev Ulmas Mustafoevich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This study presents a morphometric and histological analysis of urinary bladder polyps and papillomas. Specimens collected from cystoscopic biopsies were studied to determine their cellular composition, epithelial-stromal relationships, and structural features using hematoxylin-eosin staining and morphometric imaging software. Results indicate key differences in epithelial thickness, vascularization, and inflammatory infiltration between polyps and papillomas. These findings support the importance of detailed tissue analysis in the differential diagnosis of bladder lesions.